2020
DOI: 10.1097/pcc.0000000000002133
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis and Associated Mortality in Neonates With Congenital Heart Disease: A Multi-Institutional Study

Abstract: Objective: There are scarce data about the prevalence and mortality of necrotizing enterocolitis in neonates with congenital heart disease. The purpose of this study is to provide a multi-institutional description and comparison of the overall prevalence and mortality of necrotizing enterocolitis in neonates with congenital heart disease. Design: Retrospective multi-institutional study. Setting: The Pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Incidence rates are estimated at 3-15% (2), whereas 7-20% of all NEC cases occur in term infants (3). Velazco et al (4) identified CHD in almost 20% of NEC patients with a birth weight of more than 2,500 g. NEC prevalence in patients with congenital heart disease (CHD) is estimated at 3.7% (5). Nowadays, incidence rates are decreasing due to specialized preventive care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence rates are estimated at 3-15% (2), whereas 7-20% of all NEC cases occur in term infants (3). Velazco et al (4) identified CHD in almost 20% of NEC patients with a birth weight of more than 2,500 g. NEC prevalence in patients with congenital heart disease (CHD) is estimated at 3.7% (5). Nowadays, incidence rates are decreasing due to specialized preventive care (2).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions, such as atelectasis (incomplete lung expansion), respiratory distress of the newborn, chronic respiratory disease, and lung hypoplasia (listed within the congenital malformation category), could be due to prematurity and/or may be related to anomalies affecting diaphragm and lung development preventing adequate lung development and expansion (Dominguez & Alvares, 2018;Gallacher, Hart, & Kotecha, 2016). Similarly, both preterm birth and birth defects are associated with NEC, which ranked higher as a cause of death in our study population than among all live births in the US population (Fullerton et al, 2017;McElhinney et al, 2000;Rose & Patel, 2018;Spinner et al, 2020). In our study, a higher proportion of infants with lung hypoplasia/dysplasia and NEC listed among the causes of death were born preterm compared to the preterm proportion in the overall cohort of infants with birth defects that died during the first year of life.…”
Section: Discussionmentioning
confidence: 79%
“…Birth defects affect about 3% of infants in the United States (US), and an estimated 5-8% of live born infants with birth defects will die in infancy, compared to approximately 0.6% of live born infants in the US (Agha, Williams, Marrett, To, & Dodds, 2006; Centers for Disease Control and Prevention [CDC], 2008;Heron, 2019;Texas Department of State Health Services, 2013). Infants with a birth defect have an increased likelihood of being born preterm or low birthweight (Baer et al, 2019;Miquel-Verges, Mosley, Block, & Hobbs, 2015;Rasmussen, Moore, Paulozzi, & Rhodenhiser, 2001;Swanson & Sinkin, 2013) and developing necrotizing enterocolitis (NEC) and sepsis (Ascher et al, 2012;Fullerton et al, 2017;McElhinney et al, 2000;Spinner et al, 2020). For some defects, surgery and extended hospital-based care may be necessary, increasing the risk of surgery-related complications and nosocomial infections (CDC, 2007;Adams-Chapman et al, 2013;Colvin & Bower, 2009;Moffitt, Case, Farag, & Canfield, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With ischemic intestinal necrosis secondary to heart disease, the colon is the most commonly involved site. Hypoplastic left heart syndrome, truncus arteriosus, aortic arch obstruction and aortopulmonary window account for most cases of cardiogenic ischemic intestinal necrosis [25]. I propose that this disease should be classified as an individual entity and not be diagnosed as “NEC.” A more apt diagnostic moniker would be “cardiogenic ischemic necrosis of the intestine.”…”
Section: Diseases Commonly Diagnosed As Necmentioning
confidence: 99%